Zmienna tolerancja żywienia drogą przewodu pokarmowego u dziecka z zespolem Arnolda i Chiariego - opis przypadku - Rekowska, Martyna; Adamska, Inga; Szaflarska-Popławska, Anna; Gawryjołek, Julia; Jakubczyk, Marlena; Krogulska, Aneta; Czerwionka-Szaflarska, Mieczysława (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Feeding disorders are diagnosed in up to 90% of patients with chronic neurological diseases. We present a case of infant with Arnold-Chiari syndrome who was hospitalized several times in the clinic because of feeding difficulties. The patient had variable tolerance of nutrition through the digestive tract (oral, gastric and enteric feeding), periodically requiring the use of the parenteral nutrition. In our patient, despite performed diagnostic tests, the cause of disorders remains unknown. Adapting the methods of nutrition to the patient, however, resulted in remaining good nutritional status, helped to conduct rehabilitation and eventually enabled exclusive oral feeding. In patients with chronic neurological diseases, constant dietetic care is needed with assessment of nutritional status and feeding methods. In the case of feeding disorders, especially manifesting with dysphagia, chronic enteral feeding should be considered. Periodic parenteral nutrition is indicated in the case of intolerance of enteral feeding.